Marketing urbanistyczny w wybranych gminach województwa lubelskiego - Polska, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article takes up a new subject - question of building an urban marketing. This is one of a wide range of segments of territorial marketing which has taken a lot from business marketing. It has not been polished up yet. However, it is a useful instrument for increasing attractiveness of an area for all its actual and potential users. Its important segment is urban marketing directed to increase attractiveness of all urban "products". It can also be used in rural communities, mainly in those being under urbanization process.The author has chosen two rural communities in lubelskie voivodship which have different but still important potentials of development and urbanization. Their self-governments implement some elements of urban marketing. Previous actions have been fragmentary but clearly distinguished in lubelskie region. Marketing products created in both communities comprise of project and investment sphere. Both communities have got a complete set of documents widely concerns policy of development assistance and spatial arrangement as well as local operational programmes.The wealthier community of Terespol tries to take advantage of its border localization assets and arranged border passages as well as touristic quality. The community has got complex technical infrastructure with large reserves for potential users. It is also going to arrange a new administrative and service centre.The poorer community - Wąwolnica attempts to join the turistic system of Kazimierz nad Wisłą and the health resort in Nałęczów. It is also going to build a water reservoir on the river Bystra for the recreation needs. Both communities want to attract attention by undertakings of an extensive importance. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 707-714